Das Rätsel allgemeinfaktischer Interpretationen im Aspektsystem des Russischen / Olav Mueller-Reichau - Mueller-Reichau, Olav (Harrassowitz Verlag, 2018)
As a reference to individual, completed events, one encounters not only perfective but also imperfective verb forms in Russian-language texts. This so-called "general factual" interpretation of the imperfective is usually described as a strategy to avoid the perfect. The imperfective aspect is chosen when the outcome of the action is not to be emphasized, when the spatiotemporal circumstances surrounding the event are of no interest, when the target state of the event is not relevant In short, if only the pure fact is to be communicated that the event has taken place. But what is the positive content of general factual statements? What is relevant instead of the action result? What is actually supposed to be communicated that the event has taken place? Mueller-Reichau puts in of his study shows that general factual imperfectives refer in a systematic way to conventionalized rules in the background knowledge of the speech act participants ass the consequences of the rule activated in each case apply to the subject referent. The positive purpose of general factual statements is that attention is drawn to precisely this implicit information.
9.7 Existenzielle Imperfektiva aktivieren Regeln
Keywords: Russian language -- Aspect.; Russian language -- Verb.; Russe (Langue) -- Aspect.; FOREIGN LANGUAGE STUDY / Russian; Russian language -- Aspect; Russian language -- Verb